Atomic Pathways of Crystal-to-Crystal Transitions and Electronic Origins of Resistive Switching in MnTe for Ultralow-Power Memory - Rui Wu; Nian-Ke Chen; Ming-Yu Ma; Bai-Qian Wang; Yu-Ting Huang; Bin Zhang; Xian-Bin Li (Nanomaterials)
In conventional phase change memory (PCM) technology, the melting process required to create an amorphous state typically results in extremely high power consumption. Recently, a new type of PCM device based on a melting-free crystal-to-crystal phase transition in MnTe has been developed, offering a potential solution to the problem. However, the electronic and atomic mechanisms underlying this transition remain unclear. In this work, by first-principles calculations, the resistance contrast is attributed to the differences in hole effective mass and vacancy formation energy of the two phases. Moreover, two phase transition pathways of the α-MnTe-to-β-MnTe transition, namely, the ‘slide-and-stand-up’ transitions, are identified based on coherent atomic movements. The energy barriers for the two pathways are 0.17 eV per formula unit (f.u.) and 0.38 eV/f.u., respectively. Furthermore, the energy barriers can be reduced to 0.10 eV/f.u. and 0.26 eV/f.u. via c-axis tensile strains, which makes the phase transition easier. The current result provides new insights into the non-melting phase transition process in MnTe, facilitating the development of low-power PCM technology.